2018
DOI: 10.1016/j.actbio.2017.11.037
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic properties of human pancreatic tumors and in vitro constructs to mimic mechanical properties

Abstract: Understanding tumor-stroma crosstalk in pancreatic ductal adenocarcinoma (PDAC) is challenged by a lack of stroma-mimicking model systems. To design appropriate models, pancreatic tissue must be characterized with a method capable of evaluating in vitro models as well. Our indentation-based characterization tool quantified the distinct viscoelastic signatures of inflamed resections from pancreatitis, tumors from PDAC, and otherwise normal tissue to inform development of mechanically appropriate engineered tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
82
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(99 citation statements)
references
References 84 publications
(69 reference statements)
5
82
2
Order By: Relevance
“…In this study, we explore the applicability of indentation at this mesoscale to hydrated, soft matter samples. We and others have developed custom equipment capable of performing indentations at the mesoscale, [7][8][9][10][11][12][13][14] but translating force-displacement data derived from indentation into intrinsic mechanical properties remains a contentious process. As many have argued, Hertz contact models originally developed to derive an elastic modulus from indentation data on hard, elastic materials are inadequate to quantify intrinsic mechanical properties for soft matter.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we explore the applicability of indentation at this mesoscale to hydrated, soft matter samples. We and others have developed custom equipment capable of performing indentations at the mesoscale, [7][8][9][10][11][12][13][14] but translating force-displacement data derived from indentation into intrinsic mechanical properties remains a contentious process. As many have argued, Hertz contact models originally developed to derive an elastic modulus from indentation data on hard, elastic materials are inadequate to quantify intrinsic mechanical properties for soft matter.…”
Section: Introductionmentioning
confidence: 99%
“…When the indentation probe comes into contact with the indentation sample and the stage is moved downward, the sample causes the cantilever to bend upward relative to the rest of the piezo-electric stage structure, which reduces the gap between the edge of the cantilever's top surface and the capacitive sensor. [1] manual coarse z-stage, [2] vertically positioned piezo-electric x-stage, [3] manual z-stage, [4] rectangular aluminum beam holder for [5] capacitive sensor, [6] indentation probe, [7] manual xy-stage with transparent acrylic surface, and [8] grounded wire connected to cantilever. (B) View of indentation device with all of its components: [9] Piezo-electric stage servo controller, [10] capacitive sensor compact driver, and [11] USB DAQ module for communication with controlling PC.…”
Section: Apparatus and Principle Of Operationmentioning
confidence: 99%
“…However, for biological tissue and compliant biomaterials, apparent elastic moduli can vary across three orders of magnitude for a single tissue type depending on characterization technique and testing parameters. 2,3 AFM is often used for mechanical characterization of biological tissue and other soft matter at the ~100 nm -10 µm scale. 4 Though extensive work has been put into creating standardized procedures, 5 nano/microscale indentation is problematic for tissue-scale characterization as nano/microscale indentations quantify properties of a very specific region of a cell, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…As such, hydrogels capable of recapitulating the dynamic landscape of extracellular microenvironment are of great importance for fundamental understanding of matrix-induced aberrant cell-matrix interactions [62, 63]. Recent work has shown that the stiffness of malignant PDAC tissues ranges from 2–6 kPa in shear modulus (equivalent to ~6–18 kPa in Young’s Modulus), whereas that of the healthy tissue is around 1 kPa [64]. Synthetic approaches commonly used to mimic a stiffening tissue often rely on performing secondary crosslinking within the primary cell-laden hydrogels [62].…”
Section: Dynamic Hydrogels To Probe Pdac Cell Fatementioning
confidence: 99%